Fitrah dalam Pendidikan Islam Menurut Hasan Langgulung - Fadilah Fadilah; Ridwan Tohopi (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This research examines Hasan Langgulung 's perspective of Fitrah in Islamic education. This research is intended to analyze Hasan Langgulung 's essence of Islamic education and analyze the growth of Fitrah potentials from Hasan Langgulung 's perspective on Islamic Education. This research is a research library utilizing content analysis. The results of the research revealed that 1) According to Hasan Langgulung, Fitrah is the original power buried in humans from birth, which will become a driving force and determinant of personality and service tools. 2) The potential of Fitrah in Islamic education from Hasan Langgulung 's perspective is an interaction between potential and culture, the possibility of religion that complements humans from birth, promoting the establishment of Islamic civilization. 3) The capacity of Fitrah and Gharizah requires humans to continually learn from their surroundings and the ability to think and choose (good and bad) to decide their course of life. This research shows that improving Fitrah 's potential can be an Islamic education model that can see students' different potential paths. It may also establish formal and informal education. The growth of the capacity of Fitrah by students, teachers, and parents, therefore, seeks to instill good behavior because nature does not evolve by itself. The principle of Fitrah also demands that Islamic education strive to guide instruction for a healthy human connection with God.